Effect of work on utilization of cereal crop residues by oxen - Soller, H.; Reed, J.D.; Butterworth, M.H. (Elsevier, 1991)
Presents the results of a study in which four experimental groups of East African Shorthorned Zebu and Holstein Friesian X Boran crossbred oxen were subjected to a working exercise of pulling sleds; compares the periods of low and high work with the pre-work and post-work periods in terms of feed and water intake, body weight, digestibilities of organic matter and neutral detergent fibre, and nitrogen balance of oxen when fed a diet based on cereal crop residues.